Essential work of fracture of ruber-modified polyamide 6 in impact - Lievana, Emilio (2004)
In this paper the impact fracture behavior of two commercial, 10% and 25%, rubber-modified polyamide 6 grades is investigated by the Essential Work of Fracture methodology, which implies the testing of a series of samples of different ligament lengths and the determination of the total fracture energy. The study is based on data obtained from specimens made either from thick injected plates or bars. Tests were carried out under Charpy and Izod configuration. Two modes of fracture were displayed by the blends: ductile fracture or mixed mode depending on rubber content, processing conditions and ligament lengths of the samples. When samples displayed completely stable crack propagation behavior and geometric similarity of loaddisplacements diagrams, an essential work of fracture value wIe, independent of specimen thickness and testing configuration, could be extrapolated